Pelatihan Teknik Teknik Proteksi Instalasi Listrik Sebagai Upayah Pembinaan UMKM Kelom Geulis Tasikmalaya dalam Bidang Keselamatan Kerja - Hiron, Nurul (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
This program is a service for the Tasikmalaya home industry community in implementing technology for Community Development (IbBM) presented by LPPM-PMP of Siliwangi University. The partner in this program is a home industry that produces typical Tasikmalaya footwear made from wood waste known as ?kelom geulis?. This home industry is located in Tasikmalaya, West Java province. The problem of partners found in the field is the high electricity consumption caused by lack of electrical installation protection systems skill and knowledge. The solution offered in this program is training of protection installation of electrical sistem. The target of the trainning is employee and owners of partmer. The results of this program, through training and focus group discussions, after testing with 15 questions from the training participants, it was found that the partners had very little understanding in understanding electricity protection for small industries. After the training, there is 60% progress increasing rate of knowledge and skill of participants from the initial ability before the partners attend training and coaching.